Impressions on University of Edinburgh "Library Knowledge Exchange Week (KEW) 2016" - Özhan Sağlık (Türk Kütüphaneciliği)
University of Edinburgh, organized a program themed "Library Knowledge Exchange Week" with the aim of sharing the knowledge of archivists and librarians who came from different areas of Europe. The author of this paper attended the program on behalf of Istanbul University. We hope that the impressions and discussions shared in this paper regarding the program will raise and create awarrenss in our country.